The reliability of measuring left ventricular ejection fraction by radionuclide cardiography: evaluation by the method of variance components. Issue 6 (June 1988) - Høilund-Carlsen, P F; Lauritzen, S L; Marving, J; Rasmussen, S; Hesse, B; Folke, K; Godtfredsen, J; Chraemmer-Jørgensen, B; Gadsbøll, N; Dige-Petersen, H
Abstract : A statistical model based on the method of variance components was applied to obtain confidence statements for single and repeat determinations of left ventricular ejection fraction by radionuclide techniques. With this approach variance caused by individual factors in the measurement procedure is estimated to allow calculation of confidence intervals based on single measurements and the detection limits for changes. Six study groups made up of a total of 143 subjects were examined by both multigated equilibrium and first pass imaging. Under favourable conditions (with an updated gamma camera and experienced observer) the 95% confidence interval with a single measurement of left ventricular ejection fraction by equilibrium imaging was +/- 3 ejection fraction units, compared with +/- 6 units with the first pass technique (one ejection fraction unit = 1/100 of the possible values from 0.00 to 1.00). The minimal significant changes (at the 5% level) in measured equilibrium left ventricular ejection fraction at intervals of 15 min, 3 days, 1, 3, and 4 weeks were +/- 4, +/- 4, +/- 5, +/- 5, and +/- 6 units, respectively. The corresponding minimal detectable changes in a subject's "true" left ventricular ejection fraction for the same intervals were +/- 7, +/- 7, +/- 10, +/- 10, and +/- 12 units respectively. With first pass imaging, only average values for the variation at repeat determination could be calculated. The minimal significant change in measured first pass left ventricular ejection fraction was +/- 7 units, and the minimal detectable change in "true" left ventricular ejection fraction was +/- 14 units. Measurements of left ventricular ejection fraction by equilibrium technique were generally more reproducible than first pass determinations because the variability caused by study acquisition, observer analysis, and residual errors was smaller. The method of variance components appears to be well suited to the evaluation of quantitative biological measurements in clinical use. The popularity of established procedures may obscure the lack of basic information about method evaluation.